Análisis de riesgo de la información en la infraestructura tecnológica para el Gobierno Autónomo Descentralizado del cantón Ventanas - Reyes Guerrero, David Manuel (2017)
At present, many companies, both public and private, have technological implements for the performance of certain tasks, called these implements as technological infrastructure, being the technological infrastructure fundamental part in a company, since it facilitates the work of the employees that in it labor The technological infrastructure is very necessary, as companies increasingly work with greater volume of information, and these technologies minimize the effort of employees, providing them with ease and speed for the completion of their work, making it possible to share information through network, thus allowing communication between the devices of the company. Many companies rely on information, because it is an indispensable asset to continue to work, for this reason companies face multiple insecurities that are provided by a variety of sources, that those in charge of security in the company must control, so as not to lose the confidentiality, integrity and availability in the company's technological infrastructure, as this could affect the performance of the company's activities. Nowadays, information security problems are one of the most mentioned, since they can suffer from the biggest companies, as well as the smallest, and even more those with information related to financial areas. The Autonomous Municipal Decentralized Municipal Government of the Canton Ventanas, is a public entity, which deals with a high volume of information and a lot of importance, for this reason malicious people can be targeted by computer attacks.